A Density Functional Theory Study Evaluating the Cooperative and Synergic Effects Between (RuO2)4 and (Fe2O3)2 Clusters in Mixed (RuO2)4–(Fe2O3)2 System on the Dissociation of Water - Loghmani, Nazanin; Farrokhpour, Hossein; Hadadzadeh, Hassan; Mosallaei, Hamta (Journal of physical chemistry. C, 2025)
The dissociation of water has been identified as one of the crucial reactions in evolving H2 and O2 as clean fuels in many investigations. Studying the cooperative and synergic effect between RuO2 and Fe2O3 on the performance of RuO2–Fe2O3 toward the water dissociation reaction is the subject of our research in the present work. The first computational investigations of the water dissociation from the energy point of view on the mixed RuO2–Fe2O3 system, (RuO2)4–(Fe2O3)2, compared to the isolated RuO2 and Fe2O3 clusters are presented using the density functional theory method in both gas and water phases. The lowest values of the calculated activation energy (E a) for the dissociation of water on (Fe2O3)2, (RuO2)4, and (RuO2)4–(Fe2O3)2 in the gas phase are 9.44, 26.29, and 6.90 kcal/mol, while those in water are 8.55, 14.42, and 1.45 kcal/mol, respectively. The E a of the dissociation of water molecule on the isolated (RuO2)4 cluster with the assist of one molecule reduced to 17.78 and 13.31 kcal/mol in the gas and water phases, respectively. The DFT calculations showed that the cooperative and synergic effect between (RuO2)4 and (Fe2O3)2 on (RuO2)4–(Fe2O3)2 significantly reduce the activation energy required for water dissociation. Also, it was demonstrated that the electrostatic field of water as the solvent has a strong effect on the decrease in the E a value of the water dissociation for some pathways compared to the gas phase. The spin density surfaces of the TS structures of some selected pathways were calculated to explain the reason for the decrease of the E a value of the water dissociation on (RuO2)4–(Fe2O3)2 compared to the isolated cluster in the electrostatic field of water.